Belarus Heat Tariff Reform and Social Impact Mitigation - Zhang, Fan.; Hankinson, Denzel, 1971- (Washington, D.C. : The World Bank, 2015)
The Government of the Republic of Belarus (GoB) plans to increase district heating tariffs to cost-recovery levels and gradually phase out subsidies, replacing them with social assistance programs. Residential DH tariffs in Belarus are currently at roughly 10-21 percent of cost-recovery levels. DH subsidies are highly regressive, add costs to business, and create significant fiscal risks and macroeconomic vulnerabilities. The study analyzes the social, sectoral, and fiscal impacts of the proposed tariff reform, and identifies and recommends measures to mitigate adverse impacts of district heating tariff increases on the households. The analysis shows that a negative social impact is manageable if a tariff increase is accompanied by countervailing measures to compensate for the loss of purchasing power, in particular of the poor, through targeted social assistance and energy efficiency programs. The reform is more likely to be successful if communication campaigns to address consumer concerns are carried out before significant price increases, and consumer engagement and monitoring systems are established. When tariff reform and mitigation measures are properly sequenced and coordinated, the reform will become more socially acceptable, consumers will benefit from better quality of services, the government will achieve positive fiscal savings, and the DH sector will become sustainable in the long term. The study analyzes the social, sectoral, and fiscal impacts of the proposed district heating tariff reform in Belarus, and identifies and recommends measures to mitigate adverse impacts of district heating tariff increases on the households.
A.6 Fiscal Cost of District Heating Subsidies, 2005-12
Description based upon print version of record.
English
Includes bibliographical references.
Description based on print version record.
Keywords: Tariff -- Belarus; Heating -- Government policy -- Belarus; Subsidies -- Belarus